Quota Formula Review : Further Considerations. (Policy Papers; Policy Paper ;, 2012)
The Executive Board has held three formal meetings on the quota formula review, and discussions have also taken place in other fora including the IMFC Deputies work stream and the G-20 IFA Working Group. Considerable progress has been made in terms of identifying areas of common ground as well as those areas where views differ. At their most recent meeting in late September, Directors reaffirmed their commitment to completing the review by January 2013, and stressed that achieving this goal will require constructive engagement and a spirit of flexibility and compromise from all sides. At its subsequent meeting in Tokyo, the IMFC called on the membership to develop the consensus needed through further engagement of the Executive Board, with input from the IMFC Deputies, to complete the review by January 2013.